PENGARUH MODEL PROJECT BASED LEARNING BERBASIS OUTDOOR STUDY TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA SD - Mita Pratiwi; Evinna Cinda Hendriana; Erdi Guna Utama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the influence of the outdoor study-based project based learning model on improving students' critical thinking skills in elementary school science learning. The type of research used is quantitative research using a quasi-experimental design method (quasi-experiment) with a pretest-posttest control group design. The population in this study was all class V of SDN 85 Singkawang. The type of sampling in this research is Probability Sampling, which is a sampling technique which provides equal opportunities for the entire population selected to be the sample. The samples taken in this research were class VA as an experimental class with 30 students and class VB as a control class with 30 students. The data collection technique uses a test technique in the form of essay questions containing indicators of science critical thinking abilities and a non-test technique in the form of observing the implementation of the project based learning model based on outdoor study. The data analysis technique uses a two-sample t test, N-Gain and Percentage to observe model implementation. The results of the research stated (1) The Project Based Learning learning model based on Outdoor Study had a moderate effect on students' critical thinking abilities in class V science learning at SDN 85 Singkawang (2) There was a moderate increase in students' critical thinking abilities after implementing the Outdoor Based Project Based Learning model Study in class V science learning at SDN 85 Singkawang (3) Implementation of the Project Based Learning learning model based on Outdoor Study was carried out well in class V science learning at SDN 85 Singkawang